BL_GERICHTE 730 2013 171 / 109 vom 9. Mai 2014 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 9. Mai 2014 (730 13 171 / 109 und 730 13 368 / 110) - BL Gerichte (2014)
Prämien